Effect and Safety of Pioglitazone-Metformin Tablets in the Treatment of Newly Diagnosed Type 2 Diabetes Patients with Nonalcoholic Fatty Liver Disease in Shaanxi Province: A Randomized, Double-Blinded, Double-Simulated Multicenter Study - Fu Jianfang; Xiao Wanxia; Gao Xiling; Xu Jing; Yang Wenjuan; Liu Jianrong; He Qingzhen; Ma Kaiyan; Lian Jingxuan; Chen Taixiong; Xu Qian; Li Mengying; et al. (Journal of Diabetes Research)
Objective. The aim of study was to evaluate the effect and safety of pioglitazone-metformin combined treatment in the newly diagnosed type 2 diabetes patients with nonalcoholic fatty liver disease. Methods. A total of 120 newly diagnosed type 2 diabetes patients with nonalcoholic fatty liver disease from 8 centers were randomly divided into the control group (metformin hydrochloride) and the test group (pioglitazone hydrochloride and metformin hydrochloride). Results. Compared to the control group, after treatment, the proportion of people with mild and moderate fatty liver increased, and the proportion of people with severe fatty liver decreased, and this change was more obvious in the population with moderate and severe fatty liver. The level of γ-GT decreased in both groups before and after treatment, which was statistically significant, and there was also a statistically significant difference in the level of γ-GT between the two groups after 24 weeks. There were no significant statistically differences in blood lipid, body weight, and waist circumference between the test group and the control group. Logistic regression analysis found that BMI is one of the risk factors for fatty liver. There was also no significant difference in the incidence of serious adverse events between the two groups (control group: 10.00% and test group: 6.67%, P=0.74). Conclusion. Combined treatment with pioglitazone-metformin can effectively reduce liver fat content and gamma-GT level in newly diagnosed diabetic patients with nonalcoholic fatty liver disease, and adverse events do not increase compared with the control group, showing good safety and tolerance. This trial is registered with ClinicalTrials.gov NCT03796975.